PENGARUH PEMANFAATAN INTERNET TERHADAP KEGIATAN BELAJAR SISWA SMA DI SURAKARTA - Sri Tomo, Yustina Retno Wahyu Utami (STMIK Sinar Nusantara, 2016)
Demands that must be implemented high school in the implementation of the learning process that utilizes information and communication technologies face many obstacles that are not simple. The main problem often faced by the school is a limitation of infrastructure, human resources and learning resources. While from the teacher pengampu is limited knowledge regarding upplementary eaching materials, and motivation of teachers in the use of Internet for learning. This study aimed to examine the use of the internet by high school students as a learning support and its influence on learning motivation of high school students in the city of Surakarta. In conducting this study used methods: the spread of the questionnaire for the data pengamblan further statistical analyzes were erformed with a validity test, reliability test, test normalization and normalization. The result showed that the use of the internet and motivation to learn positive effect on student learning activities Keywords : internet, motivasi belajar, pembelajaran